Hyperacute gastric perforation: A rare presentation in the post-operative period - Kumar, Shailesh; Alam, Mohammad Sarwar; Akbal, Shazid; Chaudhary, Tayod Kumar (Indian Journal of Case Reports, 2019)
Stress-related gastric ulceration and their perforation have become history because of the research and development of highly effectiveanti-ulcer drug and their affordability and availability across our country. We present an interesting and thought-provoking case of a46-year-old female, with stress-related gastric perforation who developed the complication in a span of only 2 days of physiological insult.